Bitter Melon Extracts Enhance the Activity of Chemotherapeutic Agents Through the Modulation of Multiple Drug Resistance. Issue 12 (15th October 2013) - Kwatra, Deep; Venugopal, Anand; Standing, David; Ponnurangam, Sivapriya; Dhar, Animesh; Mitra, Ashim; Anant, Shrikant
<x xml:space="preserve">Abstract</x> Recently, we demonstrated that extracts of bitter melon (BME) can be used as a preventive/therapeutic agent in colon cancers. Here, we determined BME effects on anticancer activity and bioavailability of doxorubicin (DOX) in colon cancer cells. BME enhanced the effect of DOX on cell proliferation and sensitized the cells toward DOX upon pretreatment. Furthermore, there was both increased drug uptake and reduced drug efflux. We also observed a reduction in the expression of multidrug resistance conferring proteins (MDRCP) P‐glycoprotein, MRP‐2, and BCRP. Further BME suppressed DOX efflux in MDCK cells overexpressing the three efflux proteins individually, suggesting that BME is a potent inhibitor of MDR function. Next, we determined the effect of BME on PXR, a xenobiotic sensing nuclear receptor and a transcription factor that controls the expression of the three MDR genes. BME suppressed PXR promoter activity thereby suppressing its expression. Finally, we determined the effect of AMPK pathway on drug efflux because we have previously demonstrated that BME affects the pathway. However, inhibiting AMPK did not affect drug resistance, suggesting that BME may use different pathways for the anticancer and MDR modulating activities. Together, these results suggest that BME can enhance the bioavailability and efficacy of conventional chemotherapy. Published 2013. This article is a U.S. Government work and is in the public domain in the USA. 102:4444–4454, 2013